Disordered eating attitude and associated factors among late adolescent girls in Gondar city, northwest Ethiopia: a community-based cross-sectional study - Engdyhu, Betlihem Muche; Gonete, Kedir Abdela; Mengistu, Berhanu; Worku, Netsanet (Frontiers in Public Health, 2024)
Background Disordered eating attitudes are characterized by abnormal beliefs, thoughts, and feelings regarding food and weight control. Dieting, intentional weight loss, and weight control affect 41–62% of girls worldwide. However, there is limited information related to disordered eating attitudes and associated factors among late adolescent girls in Ethiopia, including in the study area. Thus, the study aimed to assess disordered eating attitudes and associated factors among late adolescent girls in Gondar city, northwest Ethiopia. Methods For this community-based cross-sectional study, which was conducted from 26 June to 26 July 2022, in Gondar city, Ethiopia, 1,188 adolescent girls were included. Multistage stratified sampling followed by a systematic random sampling technique was applied to recruit participants for the study. Data were collected using an interviewer-administered questionnaire containing the Eating Attitudes Test-26 (EAT-26). Anthropometric measurements were also taken. Bivariable and multivariable logistic regressions were employed to identify factors associated with disordered eating attitudes. In the final model, variables with a p-value of < 0.05 were considered statistically significant. Results A total of 1,158 late adolescent girls (a response rate of 97.5%) participated in the study. The prevalence of disordered eating attitudes among late adolescent girls was 9.7% [95% confidence interval (CI): 7.96, 11.4%]. Having a mother who was unable to read and write [adjusted odds ratio (AOR): 3.88 (95% CI: 1.07, 14.11)], having a mother who could read and write [AOR: 4.31: (95% CI: 1.14, 16.24)], having a father who only attended primary school [AOR: 3.78 (95% CI: 1.33, 10.78)], having severe anxiety [AOR: 3.26 (95% CI: 1.42, 7.49)], and severe usage of social media [AOR: 2.80 (95% CI: 1.22, 6.46)] were factors significantly associated with disordered eating attitudes among late adolescent girls. Conclusion This study revealed that disordered eating attitudes among late adolescent girls were relatively high. The educational status of parents, anxiety, and severe usage of social media were positively associated with disordered eating attitudes. Therefore, nutritional education for parents of adolescents who are vulnerable to unhealthy behavior is imperative. The finding also implied the importance of an inclusive strategy to mitigate the emerging problem of targeting vulnerable groups.